Riemann-Liouville and Higher Dimensional Hardy Operators for NonNegative Decreasing Function in Lp(·) Spaces - Muhammad Sarwar; Ghulam Murtaza; Irshaad Ahmed (Abstract and Applied Analysis)
One-weight inequalities with general weights for Riemann-Liouville transform and n-dimensional fractional integral operator in variable exponent Lebesgue spaces defined on Rn are investigated. In particular, we derive necessary and sufficient conditions governing one-weight inequalities for these operators on the cone of nonnegative decreasing functions in Lp(x) spaces.